2016
DOI: 10.1371/journal.pone.0147859
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Probiotics Affect Gastrointestinal Microbiota, Histological Structure and Shell Mineralization in Turtles

Abstract: Probiotics are widely used in nutrition, and their mode of action is intensively studied in mammals and birds; however, it is almost unknown in reptiles. In the present study, Trachemys scripta scripta and Sternotherus odoratus were used to assess the effects of dietary probiotics on chelonian gastrointestinal tract microecology. In the first, 20-week experiment, 40 young T. s. scripta were randomly distributed to four experimental groups: 1st, (CON)–with no additives; 2nd, (SSPA) with Bacillus subtilis PB6; 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 58 publications
0
20
1
Order By: Relevance
“…After washing, filters were rinsed gently in distilled water, air-dried, and mounted on slides with VectaShield (Vector Laboratories Inc., Burlingame, CA, US), an anti-fading agent containing DAPI (4',6-diamidino-2-phenylindole). To distinguish bacteria from other particles in the ileal samples (DAPI), filters were left at 4°C for 1 h in the dark until visualization with a Carl Zeiss Microscope Axio Imager M2 (Carl Zeiss Jena GmbH, Jena, Germany), as described elsewhere [34,35]. A detailed FISH protocol is presented in the Fig A in S1 File.…”
Section: Methodsmentioning
confidence: 99%
“…After washing, filters were rinsed gently in distilled water, air-dried, and mounted on slides with VectaShield (Vector Laboratories Inc., Burlingame, CA, US), an anti-fading agent containing DAPI (4',6-diamidino-2-phenylindole). To distinguish bacteria from other particles in the ileal samples (DAPI), filters were left at 4°C for 1 h in the dark until visualization with a Carl Zeiss Microscope Axio Imager M2 (Carl Zeiss Jena GmbH, Jena, Germany), as described elsewhere [34,35]. A detailed FISH protocol is presented in the Fig A in S1 File.…”
Section: Methodsmentioning
confidence: 99%
“…All details of sample preparation and FISH analyses for bacteria enumeration from jejunal digesta were described by Rawski et al [31], and Józefiak et al [23]. The oligonucleotide probes used in this study are presented in Table 2.…”
Section: Analysis Of the Microbial Community And Its Activitymentioning
confidence: 99%
“…The histological analysis of ileal samples was performed according to Rawski et al [31]. Briefly, the ileal samples were fixed immediately in freshly prepared formaldehyde solution (40 g/L of formaldehyde prepared in 0.01 M PBS, pH = 7.4) and incubated 12 h. Ileal fragments were dehydrated in alcohol dilutions, stowed in xylene, and embedded in paraffin.…”
Section: Histological Analysesmentioning
confidence: 99%
“…The microbial community of the cecal content of chickens was analyzed, as described in detail by Józefiak et al [37] and Rawski et al [38]. The oligonucleotide probes used for this study are shown in Table 3.…”
Section: Microbial Community Analysis By Fluorescent In Situ Hybridizmentioning
confidence: 99%